The critical values of coupling strength of the non-self-dual Ising lattices under decimation transformation - Kaya, Tuncer (WORLD SCIENTIFIC PUBL CO PTE LTD, 2022)
In this work, the values of critical coupling strengths of the Ising lattices which are changing their lattice structure (or non-self-dual) under decimation transformations, such as the honeycomb, the triangular and the body centered cubic Ising lattices, are obtained by a modified real space renormalization group approach (RSRG). This modification is necessary to obtain a proper relation between the coupling strengths of the original and the decimated lattices. Indeed, we have achieved to obtain a proper renormalized coupling strength relation for honeycomb and triangular lattices readily, since the decimation transformation of the honeycomb lattice produces the triangular lattice or vice versa. Here, the problem of having physically untractable interactions between degrees of freedom in the renormalized Hamiltonian, which leads eventually to inevitable approximations in the treatment, except for the 1D Ising chain, has been solved with a proper approximation. Especially for the 3D Ising lattices, the physically untractable interactions appearing in the renormalized Hamiltonian make the mathematical treatment too cumbersome. As a result, there is not enough research dealing with the 3D Ising lattices using RG theory. Our approximation is based on using the simple relation ln[1 f(kappa)] similar or equal to f(kappa), which is, of course, a very relevant first-order approximation, if f (kappa) << 1. With the help of this approximation, decimation transformation process produces only pairwise interactions in the renormalized Hamiltonian instead of having four spins, six spins, or even eight spin interactions which appear naturally if all the terms are kept in the renormalized Hamiltonians of the Ising lattices in 2D and higher dimensions. Without this approximation, one cannot apply analytic RG treatment feasibly to even simple cubic lattice, let alone applying it to the body centered cubic lattice. Using this modified RG approach, the values of critical coupling strengths of the honeycomb, the triangular and the body centered cubic Ising lattices are obtained analytically as 0.6470, 0.2754 and 0.1589, respectively. Apparently, these estimations are really close to the results obtained from cumbersome exact treatments which are 0.6585, 0.2747 and 0.1575 for the honeycomb, the triangular and the body centered cubic lattices.
Keywords: Ising model; critical phenomena; renormalization group; RENORMALIZATION-GROUP; CRYSTAL STATISTICS; GRAPHENE; ORDER; MODEL; Physics